A study on the comparison of minimally invasive surfactant therapy with insure technique of surfactant therapy in preterm babies with respiratory distress in a tertiary care hospital – A prospective cohort study - Akhila, Andra; Ghoshal, Bhaswati; Mahapatra, Nepal Chandra (Indian Journal of Child Health, 2021)
Background: Respiratory distress syndrome (RDS) is a common problem in preterm babies due to surfactant deficiency. Initially, babies were given surfactant therapy by intubation, surfactant administration, and extubation (INSURE) method. Minimally invasive surfactant therapy (MIST) is a novel method of surfactant administration without intubation to spontaneously breathing preterm babies with RDS without the removal of continuous positive airway pressure (CPAP). Aim: This study aims to compare the surfactant therapy in preterm babies with RDS through MIST and INSURE technique. Methods: This prospective, observational cohort study was conducted in the neonatology unit of Calcutta National Medical College and Hospital. A total of 212 preterm babies of <37 weeks of gestation with features of RDS, who require surfactant are taken and divided into two groups. Very sick babies with congenital anomalies are excluded from the study. In MIST group (n=102), 8 Fr feeding tube is used to deliver surfactant while the baby is on CPAP. In INSURE group (n=102), surfactant is given by intubation through endotracheal tube without CPAP and extubated. Results: Mean birth weight was 1.26 kg in MIST and 1.22 kg in INSURE. Mean gestational age was 31.33 weeks in MIST and 31.11 weeks in INSURE. It was observed that there is a significant difference in terms of duration of oxygen requirement, neonatal intensive care unit stay, and surfactant spillage during administration in MIST group compared to INSURE group. However, duration of mechanical ventilation, CPAP, number of doses of surfactant, sepsis, intraventricular hemorrhage, retinopathy of prematurity, pneumothorax, bronchopulmonary dysplasia, and mortality did not show significant difference in both the groups. Conclusion: MIST is safe, feasible, and more beneficial than INSURE technique.